Variation in blood selenium and serum vitamin E in reindeer (Rangifer tarandus tarandus) described by location, husbandry, and season - Bischoff, Karyn; Finstad, Gregory; Cary, Michael; Hillebrandt, Joseph; Moiseff, Jennifer; Erb, Hollis Nancy (Rangifer, 2017)
Reindeer (Rangifer tarandus tarandus) are important livestock for arctic and subarctic herders, including those in North America, but as climate change affects traditional herding practices, alternative methods of rearing (such as captive rearing) will likely become common. Proper nutrition is critical in livestock production, but there is minimal information available on circulating nutrient concentrations in reindeer, who are adapted to a unique climate. This study looks at 2 important antioxidants. Blood and serum were taken from female reindeer from three herds: a free-ranging herd from the Seward Peninsula, Alaska (AK), during the summer, and two captive herds (one in Fairbanks, AK and one in Upstate New York (NY) during the summer and winter. Selenium (Se) and vitamin E concentrations were described stratified on season (when possible), location, and management practices (captive or free range). Herd mean values across seasons for Se ranged from 2.42 to 4.88 µmol/L. Herd mean values across seasons for vitamin E ranged from 5.27 to 6.89 µmol/L.